Prevalence of Nicotinic Stomatitis in Smokers Attending Oral Diagnosis Department in Khanzad Dental Center and Hawler Medical University –College of Dentistry - Noor Qasim Nsaif; Jamal Qader; Ali Al.zubaidee (Diyala Journal of Medicine, 2023)
Background: Tobacco smoking is considered as one of the most common risk factors for development of oral mucosal lesions which may carry a potential risk for development of oral cancer.